1976
DOI: 10.1039/f19767202143
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the reaction of hydrogen atoms with hydrogen chloride

Abstract: The reaction of hydrogen atoms with hydrogen chloride has been studied in a discharge-flow system using electron spin resonance detection of H-atoms and mass spectrometric analysis. The Arrhenius relation log (kl/dm3 mol-1 s-') = (9.6720.10)-[(13 3002700)J mol-'/2.303 RT] was obtained for the rate constant of the initial step

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
0
19
2
Order By: Relevance
“…Now we consider the real HCl reaction (40). For the simulation, we used the information from [43][44][45]: the equilibrium point was c eq = (0.198, 0.004, 0.1995, 0.001, 0.6) and the reaction rate constants of the direct reactions were k + = (10 16 , 10 16 , 1.7 × 10 11 , 1.59 × 10 8 ). This reaction system is very stiff and the equilibrium point is almost on the edge between the vertices (0, 0, 0, 0, 1) and (0.5, 0, 0.5, 0, 0).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Now we consider the real HCl reaction (40). For the simulation, we used the information from [43][44][45]: the equilibrium point was c eq = (0.198, 0.004, 0.1995, 0.001, 0.6) and the reaction rate constants of the direct reactions were k + = (10 16 , 10 16 , 1.7 × 10 11 , 1.59 × 10 8 ). This reaction system is very stiff and the equilibrium point is almost on the edge between the vertices (0, 0, 0, 0, 1) and (0.5, 0, 0.5, 0, 0).…”
Section: Discussionmentioning
confidence: 99%
“…In this subsection we consider the reaction of hydrogen chloride ( ) production [ 43 , 44 , 45 ]. This reaction mechanism includes five substances and four reactions …”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambidge and co-workers [16,17] have also studied the H + HC1 reaction and concluded that the rate is approximately doubled by heterogeneous effects. They note a difficulty in detecting the atomic chlorine product, and a low consumption of HC1.…”
Section: C1-hcl Wallmentioning
confidence: 98%
“…The early work was evaluated by Baulch et al [30] who made a recommendation for k 1b for the temperature range 2900-7000 K. In the present work, we rely on the more recent shock tube determination of Schading and Roth [47], who extended the temperature range down to 2500 K. The reaction between HCl and H (R2b) is almost thermo-neutral. It has been measured over a broad temperature range both in the forward [78][79][80][81] and reverse [48,79,80,[82][83][84][85] direction, but only Adu and Fontijn [48,81] 5 and Lee et al [83] have obtained data at temperatures higher than 500 K.…”
Section: Reaction Mechanismmentioning
confidence: 99%